MENINGKATKAN KEMAMPUAN BAHASA INGGRIS DASAR SISWA SD, SMP, & SMA DI PANTI ASUHAN AL-ARIF SERANG - Annisa Octaviani (PT Triputra Sejahtera Prima, 2023)
Many children in Indonesia have limited English language skills. Especially for children who live in an orphanage that does not have educators to teach English. This community service activity was carried out to improve the ability of students, especially elementary and junior high school students, to speak basic English at Panti Asuhan Al-Arif Kasemen Serang, Banten. The community service activity was carried out directly at the orphanage and divided into 2 groups, namely elementary and junior high school levels. Activities focused on providing materials and training provided by nine students with the direction of one Pamulang University English Literature lecturer.